2021
DOI: 10.1111/sji.13119
|View full text |Cite
|
Sign up to set email alerts
|

Immune and stromal related genes in colon cancer: Analysis of tumour microenvironment based on the cancer genome atlas (TCGA) and gene expression omnibus (GEO) databases

Abstract: The incidence of colon cancer is amongst the top three in the world. The tumour microenvironment plays an important role in the occurrence and development of colon cancer. Stromal cells and immune cells are the main components of the tumour microenvironment. Our study detected genes, which affected the infiltration of stromal, immune cells and the way they affected the prognosis of colon cancer patients. We found that the colon's immune system had a special way to affect the tumour microenvironment. Moderate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These data are consistent with previous TME analysis using multiple CRC cohorts, which demonstrated significant negative correlations of tumor purity with immune and stromal scores. 30 , 31 Finally, we analyzed our identified signature in the context of an immune and stromal gene signature related to CRC metastasis. A well-validated 292 gene expression signature associated with immune and stromal components of CRC tumors was previously described using data from TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…These data are consistent with previous TME analysis using multiple CRC cohorts, which demonstrated significant negative correlations of tumor purity with immune and stromal scores. 30 , 31 Finally, we analyzed our identified signature in the context of an immune and stromal gene signature related to CRC metastasis. A well-validated 292 gene expression signature associated with immune and stromal components of CRC tumors was previously described using data from TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al. reported that LPAR1 can mediate various biological functions of tumors ( 34 ) and participate in the activation, proliferation differentiation, and migration of immune cells ( 32 ). Our correlation analysis between the ssGSEA scores of the differentially abundant immune cells and biomarkers in this study showed that LPAR1 was positively correlated with activated CD4 T cells and effector memory CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that all these genes could contribute to the transition of in ammation and immune response and further affect response to anti-CTLA-4 ICIs [25], and these three genes were also identi ed as potential prognostic biomarkers for melanoma [26][27][28][29]. The other genes including FGFR4, GNAI1, CD36 and FLT1 could alter the tumor microenvironment and further impact ICIs' clinical e cacy, combination their inhibitors and ICIs might be better for melanoma [30][31][32][33]. Khunger et al [34] found that COL1A2 was associated with cancer development and progression, and patients with melanoma were more likely to be bene t from anti-CTLA-4 inhibitors when COL1A2 was highly expressed.…”
Section: Discussionmentioning
confidence: 99%